IT Governance Analysis and Design of Microfinance Institution Using COBIT 5 Framework Evaluate, Direct, Monitor (EDM) and Align, Plan, and Organize (APO) Domains (Case Study: PT Sarana Jabar Ventura) - Saputra, Muhammad Tamami Dwi; Alhilman, Judi; Supratman, Nurdinintya Athari; Jonathan, Fernaldi; Mulyana, Rahmat; Prasetyo, Yuli Adam (School of Industrial and System Engineering, Telkom University, 2017)
A microfinance institute (LKM/ Lembaga Keuangan Mikro) is a company that focuses in providing funds to small, early-stage, and emerging firms or small medium enterprises. A company that is engaged in financial sector and works under the surveillance of OJK/ FSA (Financial Service Authority) always has some questions whether this company really needs to implement IT Governance best practices or to what extent it does. The research in PT Sarana Jabar Ventura as one of the microfinance institutes using COBIT 5 framework for the domain of EDM (Evaluate-Direct-Monitor) & APO (Align-Plan-Organize) has shown that the existing practice is not adequate enough to align the business to IT and to manage its risk optimally so the IT solution will be beneficial for the business. Therefore, it is necessary to design the IT governance practice here, based on the seven enablers of COBIT 5 which are categorized into 3 aspects: process, people, and technology. The results of this research are design recommendations as follows: IT policy, procedures, organization structure, job description and the supporting tools and technology. It is expected that the company will implement the results in the near future. Keywords—COBIT 5, IT governance, microfinance institution